Analisis Karakter Kemandirian dalam diri Siswa Kelas XI MIA 2 dan XI MIA 3 di SMA Negeri 7 Kota Jambi - Dwi Cahya Ningsih; Mislina Mislina (Universitas Muhammadiyah Sorong, 2020)
This study aims to analyze the character of independence of class XI MIA 2 and XI MIA 3 students of SMA Negeri 7 Jambi City. This research uses descriptive quantitative research methods. While the type of research used is observation using a test assessment instrument in the form of a questionnaire with independent character variables. The subjects used in this study were 59 respondents. The data analysis technique used is descriptive statistical analysis techniques. The results of the study stated that the questionnaire for class XI MIA 2 independence was classified as '' Not Good '' and '' Good '' with a percentage of 40% of statements being answered well by students and 60% of statements being answered poorly by students. on the results of class XI MIA 3 research - the average is classified in the category of '' Good '' with the percentage of 56.7% of statements answered well by students and 0% of statements answered poorly by students. So, based on the results of the questionnaire it can be concluded that the students of class XI MIA 2 and XI MIA 3 in SMA Negeri 7 Jambi City have not been fully completed but there are also those who have the character of independence in the learning process.